Seeing Red: Terminal Description and Explanation in Linguistics - Lamarche, Jacques (Linguistica Atlantica, 2004)
This study proposes an approach to linguistic semantics under which the values of the substantive distinctions in grammar (adjective, proper noun, common noun, ec.) are not lexically specified on terms, but rather follow from the application of the rules that combine terms into sentences. At the level of the term, all substantive elements have the same value, that of "atom" or "nondecomposable unit", and their denotations (the notions they are associated to in the conceptual domain) only serve to distinguish them from one another. The categorical distinctions then emerge from how the syntactic rules manipulate a term’s basic atomic vaue. Whether the result is felicitous depends on what the term denotes in the conceptual domain. With this approach, we show how we can account for the different categorial values of the expression red (adjective, as in Mary’s favourite car is red, and common noun, as in Mary’s favourite colour is red) with a unified lexical description. The semantic value of substantive elements in grammar is thus derived, since it emerges from the application of combinatorial rules. The lexical vocabulary, which in principle cannot be derived, is thus optimal, since each form can be associated with one conceptual meaning at the lexical level.